Syncope and Its Impact on Occupational Accidents and Employment: A Danish Nationwide Retrospective Cohort Study. Issue 4 (April 2017) - Numé, Anna-Karin; Kragholm, Kristian; Carlson, Nicolas; Kristensen, Søren L.; Bøggild, Henrik; Hlatky, Mark A.; Torp-Pedersen, Christian; Gislason, Gunnar; Ruwald, Martin H.
Abstract : Background—: First-time syncopal episodes usually occur in adults of working age, but their impact on occupational safety and employment remains unknown. We examined the associations of syncope with occupational accidents and termination of employment. Methods and Results—: Through linkage of Danish population-based registers, we included all residents 18 to 64 years from 2008 to 2012. Among 3 410 148 eligible individuals, 21 729 with a first-time diagnosis of syncope were identified, with a median age 48.4 years (first to third quartiles, 33.0–59.5), and 10 757 (49.5%) employed at time of the syncope event. Over a median follow-up of 3.2 years (first to third quartiles, 2.0–4.5), 622 people with syncope had an occupational accident requiring hospitalization (2.1/100 person-years). In multiple Poisson regression analysis, the incidence rate ratio in the employed syncope population was higher than in the employed general population (1.44; 95% confidence interval [CI], 1.33–1.55) and more pronounced in people with recurrences (2.02; 95% CI, 1.47–2.78). The 2-year risk of termination of employment was 31.3% (95% CI, 30.4%–32.3%), which was twice the risk of the reference population (15.2%; 95% CI, 14.7%–15.7%), using the Aalen–Johansen estimator. Factors associated with termination of employment were age <40 years (incidence rate ratio, 1.48; 95% CI, 1.37–1.59), cardiovascular disease (1.20; 95% CI, 1.06–1.36), depression (1.72; 95% CI, 1.55–1.90), and low educational level (2.61; 95% CI, 2.34–2.91). Conclusions—: In this nationwide cohort, syncope was associated with a 1.4-fold higher risk of occupational accidents and a 2-fold higher risk of termination of employment compared with the employed general population. Abstract : Supplemental Digital Content is available in the text.